Detection of escherichia coli heat labile enterotoxin by staphylococcal co-agglutination test. - Parce, Carmina J. (1983)
A modified procedure for Staphylococcal CoAgglutination Test in microtiter plates was adapted for the detection of E. coli heat labile enterotoxin. This test detected LT from culture supernates of known ETEC strains and from the E. coli isolated from diarrhea patients. Stronger agglutination reactions were noted when 18 hour cultures were treated with Polymyxin B. LT-producing E. coli was more prevalent in infants and children below 5 years old. They were detected in 16.1 of 310 diarrhea patients who were found negative for other bacterial enteropathogens.
Thesis (Master of Science in Public Health)--University of the Philippines Manila.
Keywords: Eschirichia coli; Labile enterotoxin; Diarrhea in children